Peningkatan Minat Belajar Matematika Melalui Strategi Group Investigation Pada Siswa Kelas V SDN 2 Glagah Tahun 2015/2016 - Setyoko, Alvian, Drs.Suwarno,S.H,.M.Pd (2016)
This study aims to increase the mathematic interest fifth grade students of 2 Glagah Elementary School. This type of research is a classroom action research (CAR). The subjects in this study were teachers and fifth grade students of Majegan 3 Elementary School with twenty six students. While the object of research is applying Group Investigation learning strategy. The technique of collecting data through interviews, observation, and testing. Data analysis technique used triangulation source. The results showed an increased interest mathematics of students that includes four aspects of indicators of interest mathematics, which includes: sense of excitement in pre-cycle by 60%, the first cycle of 74% and increased in the second cycle 84%, increasing interest in 64.4% pre-cycle, the first cycle and a 79% increase in cycle II 84%, their interest in maths the 48% pre-cycle, the first cycle of 70% and increased 86.5% in the second cycle, the involvement of the students towards learning Mathematics 60% pre-cycle, the first cycle of 66% and increased 87.5% in the second cycle.Group Investigation learning strategy also increased student learning outcomes at the stage of pre-cycle there are 7students who completed KKM or 27% and increased in the second cycle there are 24 students who completed the KKM or 92%. The conclusion of this study is through the application of Group Investigation learning Strategy can increase the mathematics interest fifth grade students of 2 Glagah Elementary school of school year 2015/2016. Keywords: Interest in Learning Mathematics, Group Investigation learning Strategy.